Start-Up and Performance of Uasb Reactors Using Zeolite for Improvement of Nitrate Removal Process - Huilinir-Curio, C; Montalvo-Martinez, S (Elsevier, 2014)
A first study on the use of Chilean natural zeolite of different particle sizes (0.5, 1 and 2mm in diameter) in laboratory-scale batch denitrificant reactors was carried out with the aim of assessing the microbial communities adhered to this material. Molecular techniques such as fluorescence in situ hybridization (FISH) and denaturing gradient gel electrophoresis (DGGE) fingerprints revealed a high microbial diversity with a strong presence of Gammaproteobacteria (70% of the total microorganisms) in reactors with zeolite 0.5mm in diameter. Archaea were only detected in the reactors with zeolite 1mm in diameter. In addition, the acclimatization and start-up of two UASB reactors (one without zeolite and the other with added zeolite 1mm in diameter) were conducted following three consecutive and progressive stages using upward velocities from 0.10 to 0.44m/h in order to establish an experimental protocol suitable for the start-up of this type of reactors. Total (100%) nitrate reduction was achieved in the UASB reactors with and without zeolite on the 7th and 11th days, respectively, of the second stage of the start-up period, showing the suitability of the use of this material in this type of reactors. Finally, a third study carried out with both UASB reactors operating in continuous mode at a high organic loading rate (44kgCOD/m3d) and a very low HRT (2.5h) revealed that the reactor with zeolite achieved a nitrate removal efficiency of 92.4% at a nitrogen load of 6.42kgNO3 -/(m3d). This last study also demonstrated the robustness of the UASB reactor with zeolite under nitrate load variations. © 2014 Elsevier B.V.